Closure - Hitapriya Suprayitno (Journal of Infrastructure & Facility Asset Management, 2024)
Journal of Infrastructure & Facility Asset Management Volume 6, Special Issue 1, January 2024 (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.6, Issue 1, January 2024 Determination of Optimum Mixture Between FABA and Local Fill Soil for Road Embankment. Case study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central KalimantanRaden Hisyam Syauqi Al Ghifari, Noor Endah Mochtar & Soendiarto Analysis of Main Road Stability Due to The Effect of River Water Level Fluctuations and Rainfall (Case Study: Trengguli - Kudus Road Section)Akhdiat Fajar Wijaya Kusuma, Ria Asih Aryani Soemitro, Trihanyndio Rendy Satrya& Yanuar Dwi Putra Analysis of Existing Slope Reinforcement Design on Clay Shale Soil and Its Alternative Modifications: A Case Study of the Awunio – Lapuko Road Section Sta 4+955 – 5+015 in the Southeast Sulawesi ProvinceA. Azhari, Khoiri & Freddy Analysis of Road Embankment Improvement on Soft Soil Using Foamed Mortar Lightweight EmbankmentAlfiady Reza Permana Putuarga, Indrasurya B. Mochtar & Dedy Mandarsyah Determination of the Percentage Ca(OH)2 Lime Stabilization Material for Weathered Clay Shale as Road Subgrade on Serang – Panimbang Toll Road Section III STA 57+200Prince Joy Sormin, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo